1065. Keeping Score: Utilizing a Prioritization Tool to Create Multidisciplinary Antimicrobial Stewardship Documentation - Mediwala, Krutika N (Open Forum Infect Dis, 2019)
BACKGROUND: A multidisciplinary approach using pre-authorization and/or prospective audit and feedback combined with institutional guidelines, personnel education, and intervention monitoring is essential for successful antimicrobial stewardship programs (ASP). Assessing the impact of ASPs can be process-based and/or outcome-based. Electronic medical record-based clinical decision support (CDS) tools can be used to prioritize stewardship interventions. METHODS: The Medical University of South Carolina (MUSC) transitioned from Theradoc® to Epic® for ASP surveillance and data collection in 2018. The ASP team developed a scoring algorithm with integral rules to identify and analyze inpatients who might require ASP interventions. The dynamic list captures and scores patients based on key infection-related data and prioritizes interventions. Additionally, we created a smart form flowsheet to streamline stewardship efforts for use by physicians and pharmacists. Accuracy of event capture was assessed during the buildout and via daily comparisons between Theradoc® and Epic®. Our goals are to optimize the treatment of potentially fatal infections (e.g., bacteremia) and delay emerging resistance. RESULTS: Our ASP module utilizes a scoring algorithm to identify and prioritize patients with positive blood or central nervous system cultures, other positive critical diagnostic tests, and high-risk antimicrobial use. Additional rules identify “bug-drug” mismatches, multiple positive cultures, and de-escalation opportunities. For example, the rules assign a high priority to patients with positive blood cultures and no prescribed antibiotics, but a lower priority score to restricted antimicrobial orders. We created a smart form flowsheet to document microorganism, presumed source, anti-infective use, ASP intervention, and acceptance of recommendations, allowing for multidisciplinary documentation outside of Epic® I-vents. Finally, we created a Reporting Workbench report which allows for monthly compilation and analysis of ASP interventions. CONCLUSION: The MUSC Epic® ASP platform build showcases a CDS system that allows for streamlined, multidisciplinary communication, documentation, and analysis of outcomes. DISCLOSURES: All authors: No reported disclosures.